IMPROVEMENT THE FACILITIES AND INFRASTRCUTURE OF SERENGSENG CITY FOREST, JAKARTA - Maretha Sujana, Caroline (Bina Nusantara University, 2023)
The Serengseng city forest is locate in the center of West Jakarta. This forest is a green space used as a recreational place by the surrounding community amid the hustle and bustle of Jakarta city. Community Development Binus from the civil engineering department tried to help the Forestry Service to improve The Srengseng city forest. Some improvements to existing supporting facilities are needed to enhance the comfort of visitors. Some improvements that can do are provision the location with maps, road directions, reflectors along the walking paths, shelters, lights, and park benches.